2013
DOI: 10.14712/23362936.2014.17
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Vitamin D Deficiency and Pulmonary Hypertension

Abstract: R e c e i ve d A p r i l 1 5 , 2 0 1 3 ; A c c e p t e d A u g u s t 1 4 , 2 0 1 3 .Key words: Vitamin D -Pulmonary artery pressure -Renin-angiotensinaldosterone system Abstract: Vitamin D deficiency actives renin-angiotensin-aldosterone system (RAAS) which affects cardiovascular system. Activation of RAAS is associated with pulmonary hypertension (PHT). Relation between vitamin D deficiency and PHT could be therefore suggested. In our study we compared pulmonary artery pressure between vitamin D deficiency an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
1
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 17 publications
0
32
1
2
Order By: Relevance
“…Regarding pulmonary hypertension, Demir et al [89] estimated that there is a statistically significant difference p < 0.001) in the systolic pulmonary artery pressure in patients with low levels of vitamin D (36.31 ± 8.99 mmHg) and those with adequate serum levels (32.42 ± 8.06 mmHg). This promising result notwithstanding, currently there is not enough evidence to correlate pulmonary hypertension and vitamin D levels abnormalities.…”
Section: Methodsmentioning
confidence: 99%
“…Regarding pulmonary hypertension, Demir et al [89] estimated that there is a statistically significant difference p < 0.001) in the systolic pulmonary artery pressure in patients with low levels of vitamin D (36.31 ± 8.99 mmHg) and those with adequate serum levels (32.42 ± 8.06 mmHg). This promising result notwithstanding, currently there is not enough evidence to correlate pulmonary hypertension and vitamin D levels abnormalities.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, low vitamin D status in PAH patients could be the reason for the elevated PTH. Later, epidemiological studies demonstrated that vitamin D deficiency is quite prevalent in PAH patients [59,62,63]. In the prospective study carried out by Demir et al, PAH patients presented much lower vitamin D levels (median of 6.79 ng/mL), considered as severe deficit of vitamin D (<10 ng/mL of serum 25(OH)D 3 ), than controls (18.76 ng/mL) [62].…”
Section: Vitamin Dmentioning
confidence: 99%
“…Some preliminary evidence suggests that vitD deficiency is common in PAH [23][24][25][26]. Herein, we aimed to examine the total, bioavailable, and free 25(OH)vitD levels and their relationship with relevant clinical variables in PAH.…”
Section: Introductionmentioning
confidence: 99%